2002
DOI: 10.1002/ana.10415
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between extracellular glucose and seizure susceptibility in adult rats

Abstract: In adult diabetic patients, periods of hyperglycemia may be associated with exacerbation of focal seizures. Our objective was to determine in the adult rats the correlation between seizure susceptibility and extracellular glucose concentration in two models of seizures. Male rats were injected with two doses of streptozocin (40 mg/kg IP) on 2 consecutive days to induce diabetic hyperglycemia. Controls either received vehicle or were not injected. After 2 weeks, blood glucose concentration was measured, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
85
1
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(97 citation statements)
references
References 45 publications
6
85
1
5
Order By: Relevance
“…Researchers have proposed several hypotheses on the possible pathophysiology of their comorbidity, including immune abnormalities, brain lesions, genetic factors and metabolic abnormalities [23]. In particular, both hyperglycaemia and hypoglycaemia commonly occur in elderly people with diabetes, and can alter the balance between the inhibition and excitation of neuronal networks and cause focal motor seizures [24][25][26]. In addition, we found that younger age was associated with an increased risk of developing epilepsy.…”
Section: Resultsmentioning
confidence: 74%
“…Researchers have proposed several hypotheses on the possible pathophysiology of their comorbidity, including immune abnormalities, brain lesions, genetic factors and metabolic abnormalities [23]. In particular, both hyperglycaemia and hypoglycaemia commonly occur in elderly people with diabetes, and can alter the balance between the inhibition and excitation of neuronal networks and cause focal motor seizures [24][25][26]. In addition, we found that younger age was associated with an increased risk of developing epilepsy.…”
Section: Resultsmentioning
confidence: 74%
“…Plasma glucose measurements-Seizures are accompanied by a significant increase in plasma glucose levels (Handforth and Treiman, 1995b;Schwechter et al, 2003). What can appear as decreased metabolism postictally may be largely the competitive effects of high plasma glucose on 2 DG uptake.…”
Section: Methodsmentioning
confidence: 99%
“…Glucose level measurements were taken prior to a seizure, immediately following the seizure and 20 min after seizure induction. Blood samples were obtained from tip of the tail (∼10 μl) as described previously (Schwechter et al, 2003). The baseline value for all groups was 46 ± 4 mg/100 ml (mean ± SEM), which is relatively low because the animals did not receive food for up to 20 h before the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…However, the effects of hyperglycemia on the central nervous system (CNS) and neuronal excitability (Biessel et al, 1994;Stewart et al, 1999;Gispen and Biessel, 2000) are not fully understood. High glucose concentrations have been associated with a lower seizure threshold in an animal model with a single seizure (Schwechter et al, 2003) and neuronal excitability and seizures are related to rapid glucose utilization and glycolysis (Greene et al, 2003). Experimentally, the correlation between extracellular glucose concentration and excitability www.intechopen.com…”
Section: Epileptic Seizures In Experimental Animals With Diabetic Hypmentioning
confidence: 99%
“…The pathophysiology of epileptic seizures in DH is probably multi-factorial. Glucose itself could enhance synaptic transmission and propagation, leading to more excitable neurons (Tutka et al, 1998;Gispen and Biessels, 2000) and even epileptic seizures (Schwechter et al, 2003), regardless of the presence of organic lesions. Underlying focal ischemia has also been suggested as having a role in triggering these partial seizures (Singh and Strobos, 1989).…”
mentioning
confidence: 99%